Incorporating Multiple Intelligences in L2 Writing Classes: New Horizons in Redefining the Classroom - Haddaji, Hatem (International Journal of Language and Literary Studies, 2022)
This article seeks to restore the notion of the classroom in light of emerging pedagogies. It attempts to provide a sketchy introduction of the theory of multiple intelligences and its potential gains in ELT. Despite the variance of teaching methods and approaches implemented in classrooms, students’ results in some topics have remained below the par of teachers’ expectations. This article attempts to provide a solution to teaching students to their differences and learning preferences. It investigates the impacts of accommodating students’ intelligences profiles in writing classes. To fulfill this objective, 114 male and female participants majoring in English at the University of Kairouan were asked to write a five-paragraph essay and respond to a writing strategies questionnaire, a multiple intelligences inventory. The collected data were statistically analyzed using Pearson Correlation and ANOVA techniques to probe possible correlations and predictability levels between MI profiles and WS. The findings indicated that there is a significant degree of correlations between learners’ multiple intelligence profiles and the writing strategies they use when writing. As for the impacts of multiple intelligences on writing quality, the results revealed weak or no significant correlations. It is then suggested that the same study should be further elaborated within the same L2 context with larger population to acknowledge learners’ differences and learning preferences and benefit from new dimensions in teaching paradigms Chronic deterioration of learners results in different language topics The current upheaval caused by the striking pandemic Lack of homogeneity in the syllabi provided to university students For the above reasons, implementing the Multiple Intelligences Theory (Gardner 1983/1999) and Computer Assisted Language Learning at the university level classroom could boost the teaching/ learning and would reduce apprehension and foster learning achievements. So, knowing learners’ individual differences and preferences and integrating CALL in the classroom would allow teachers to establish “broad range of teaching strategies with their students” (Armstrong, 2009). Gardner (2006) also concludes that “people have very different kinds of minds… then education which treats everybody the same way, is actually the most unfair education”. Briefly, incorporating intelligences whether cognitive or artificial and recognizing the blended learning would revolutionize the notion of the classroom and reduce inconveniences between the teaching input and the learning output. Therefore, the new CLASSROOM would be effective, inspiring, and prospective.